2011
DOI: 10.1111/j.1365-2311.2011.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology and phylogenetic structure of a complex neotropical termite assemblage, revealed by nitrogen stable isotope ratios

Abstract: absen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 55 publications
(70 reference statements)
5
71
0
Order By: Relevance
“…These could include stored organic material, the hosts faeces and dead bodies, and the lining of the termitarium walls, which is also composed of faeces. Although still open to investigation, this assumption is in line – at least regarding I. microcerus – with previous reports by Noirot [56] and Mathews [12] and recent evidence by Bourguignon et al [32].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These could include stored organic material, the hosts faeces and dead bodies, and the lining of the termitarium walls, which is also composed of faeces. Although still open to investigation, this assumption is in line – at least regarding I. microcerus – with previous reports by Noirot [56] and Mathews [12] and recent evidence by Bourguignon et al [32].…”
Section: Discussionsupporting
confidence: 88%
“…In communities of termites, interactions with respect to food resources have been identified as an important regulating factor; examples include species assemblages from the African savannah [47], [48] and the South American tropical rainforest [32], [34].…”
Section: Discussionmentioning
confidence: 99%
“…With recent observations on E. neotenicus [15], the presence of AQS as a queen replacement strategy in the Termitidae is firmly established. Far from being restricted to temperate wood-feeding Rhinotermitidae of the genus Reticulitermes, AQS now involves two species which are tropical rainforest soil feeders [38,39] and represent distinct subfamilies of higher termites. In AQS systems, two contrasted dispersal and reproductive patterns occur simultaneously: sexually produced alates initiate new colonies after a longdistance dispersal, while asexually produced neotenics reproduce inside the mother-nest.…”
Section: Discussionmentioning
confidence: 99%
“…The categories are defined by a humification gradient, which ranges from whole plant matter (such as wood and dead leaves) to decomposed cellulosic compounds dispersed in the soil (see Donovan et al 2001 for a more detailed description). Although the classification by feeding groups is widely used, more recent studies have indicated that there is a continuum among termite feeding preferences (Bourguignon et al 2010).…”
Section: Feeding Habit Inferencesmentioning
confidence: 99%